Adubação nitrogenada e inoculação com azospirillum brasilense em híbridos de milho - Morais, Tâmara Prado de (2012)
Maize is one of the world s most important cultivated cereals; however, it presents great challenges for correct fertilization management. Its high nitrogen demand has been the major cause of excessive applications of synthetic nitrogen fertilizers in the crop. As a result, both environmental and economical problems have increased. Therefore, alternative methods that promote plant growth and ensure productivity need to be better studied to associate efficiency, economic viability and environment safety. Diazotrophic bacteria are able to fix atmospheric nitrogen and synthesize plant growth promoting substances, which may reduce the need for nitrogen fertilizers. To test this hypothesis, this work evaluated inoculation with Azospirillum brasilense combined with nitrogen fertilization on maize plants under Brazilian Cerrado conditions. The research consisted of three trials, in a randomized block design. The first experiment was done in the field at Iraí de Minas, during the crop season of 2009/2010. Four maize hybrids inoculated or not with the Azospirillum bacteria and subjected to different nitrogen rates (50, 100, 150, 200, 250 and 300 kg of N ha-1) were evaluated. The second trial, under greenhouse conditions at Uberlândia, was set up as a 3 x 3 factorial. The first factor corresponded to nitrogen rates (0, 100 and 200 kg ha-1) and the second factor to Azospirillum inoculant (0, 100 and 200 mL ha-1). At the end of this experiment, another greenhouse trial was done to determine the possible residual effect of inoculation and nitrogen fertilization. According to the field study, it was concluded that maize inoculation with Azospirillum brasilense is a promising technology capable of significantly enhancing crop yield, in both high and low investment systems. In general, greenhouse evaluations showed that nitrogen application promoted growth, increased chlorophyll and nutrient contents, and intensified the activity of rhizosphere enzymes related to ammonium and inorganic phosphorus availability in maize plants. Also, nitrogen fertilization had residual effect on plant development in the test evaluating the residual effect of the fertilizer.